Design And Characterization Of Targeted Drug Delivery Systems Of 5 Fluoro Uracil - KAVITHA K (International Journal of Pharma and Bio Sciences, 2012)
Targeted drug delivery of 5 fluorouracil enhances effective localization of the drug at gastric cancer to minimize toxic effects and maximize therapeutic index. In the present study, gastro retentive systems of 5 fluorouracil were formulated. The drug 5fluorouracil was mixed with β cyclodextrin to enhance the solubility of the drug (prepared by freeze drying technique in the ratio of 1:1, which showed a higher dissolution profile when compared to other complexes). The granules of 5FU along with other ingredients were prepared by wet granulation technique and were investigated for physical characteristics. The tablet weight, thickness, and pressure were optimized by varying the process parameters. Buoyancy determination was done by beaker method using 100 ml of Simulated Gastric Fluid (SGF), at 37°C. Invitro dissolution studies were performed with SGF and the samples were analyzed spectrophotometrically at 266 nm. Curve fitting analysis of the formulations was done to analyze the release pattern of the formulations. The best formula possessed the minimum buoyancy lag time as well as maximum floatation time of 24 hours. Invitro dissolution study showed that formulation FIX with hydroxyl propyl methyl cellulose as polymer and sodium bicarbonate as gas generating agent could show maximum release. The kinetic study confirmed that the selected formulations followed zero order release with higuchi pattern. It might be concluded that formulation of floating effervescent tablets of 5 fluorouracil was reproducible and the release could be controlled over an extended period of time. This gastroretentive formulation could target the drug to gastric tumors